Water-rock interaction during mineral carbonation and volcanic ash weathering - Helgi Arnar Alfreðsson 1984- (2015)
The reduction of atmospheric carbon dioxide (CO2) is considered one of the greatest challenges of this century. Carbon capture and storage (CCS) is one of the means proposed to lower the atmospheric CO2 content. The aim of the CarbFix project in Iceland was to design and test a CO2 re-injection system, in which CO2 from the Hellisheidi geothermal power plant was injected, fully dissolved in water, into basaltic rocks. In this way the carbon is mineralized upon basalt dissolution by the precipitation of carbonate minerals. Pre-injection study of the CarbFix site showed that the field consists of primitive basaltic rocks, both glassy and crystalline. The study further showed that the targeted aquifer contains high-pH water, ranging in temperature from 15 to 35°C, and is isolated from the atmosphere. The fluid chemistry indicated equilibrium with secondary minerals such as calcite, Ca-rich zeolites, and clays. Geochemical modelling of the injection schemes predicted that 1-2 moles of basaltic rock would be needed to lower the dissolved carbon in one kg of water back to pre-injection values by precipitation of Ca-Mg-Fe-carbonates. A syringe sampler for CO2-rich fluids and tracers was designed and tested, both in the laboratory and in the field. The sampler was used to monitor the carbonation process and the evolution of the CO2-rich fluid during the subsurface mineral carbonation. The 2010 Eyjafjallajökull eruption provided a unique opportunity to study the impact of eruption mechanism, hydromagmatic versus magmatic, on the environmental chemistry. Plug-flow experiments were conducted on pristine volcanic ash, in order to evaluate the initial leaching from the ash surface. There was a dramatic difference in pH evolution between the effluent waters from the two ash types. Within minutes there was a “chemical divide” by several orders of magnitude in the proton concentration. The effluent from the hydromagmatic ash was alkaline, but the magmatic ash effluent was acidic. The effluent from the hydromagmatic ash thus ...